Modelling and Analysis on Impeller of Centrifugal Compressor - Chandra, R. Rama; Prasad Naidu , V. Naga; Tiruchanur , Lakshmi Priya (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2017)
Impeller is a main component of the Centrifugal Compressor where it has got a series of curved vanes, fitted inside shroud plates. Impeller is a rotating part of a centrifugal compressor, or other machine designed to move a fluid by rotation, which imparts Centrifugal force to the fluid and the fluid moves radially out. This presentation deals with the 3-D solid modeling, analysis and optimization on the impeller blades which are made of “LOW CARBON STEEL”. The 3-Dimensional Centrifugal compressor impeller model has been done using “CATIA V5” software. ANSYS is used for the analysis of this model. Von Mises stress and yield strength of the model are compared in order to observed whether the design is safe for the Carbon Steel material and also the displacements of the component in X, Y and Z directions.